Fertilisation in Eucalyptus grandis on Severely Truncated Soil. III: Nutrient Uptake - Prasad, K. G.; Gupta, O. N.; Mohan, S.; Subramaniam, V.; Manivachakam, P. (Indian Forester, 1984)
Nutrient content and uptake by different components (root stem, twig and leaf) of one year old Eucalyptus grandis as affected by urea and superphosphate application at Minmutti, Kerala was estimated. In general, N, and K concentration decreased due to N and P fertiliser application either alone or in combination. However, uptake of N, P and K increased with each dose of application of N and P fertilisers and generally uptake values were maximum in N75 P75 treatments. Percent recovery of N was greater (79.1%) in N75 P75 treatment and P recovery (18.8%) In N75 P75 treatment.